Development of Scrapbook Media to Improve Critical Thinking Skills of Junior High School Students in Science Learning - Sari, Winda Raina; Nuha, Ulin (FKIP Universitas Lampung, 2023)
Critical thinking is a high-level skill that is very urgent for students. Nevertheless, the critical thinking skills of junior high school students in science learning still need to be improved. This research was conducted to produce an educational product, namely, scrapbook media in science learning to enhance the critical thinking skills of junior high school students. Researchers used the Plomp development model to collect data, including preliminary research, prototyping stage, and assessment phase. The validation results from the experts reached 86%, with very valid criteria in all four aspects. In the practicality test results from the learning implementation observation sheet, 98% of the results were obtained with convenient criteria. The result of the N-gain analysis with high criteria. Based on these results, it can be concluded that the scrapbook media in science learning to improve the critical thinking skills of junior high school students is valid, practical, and effective. Furthermore, scrapbook media can be used to facilitate students in science learning. Scrapbook media can be designed by integrating learning activities that require active students so that their critical thinking skills can develop. Students can learn to interpret, analyze, evaluate, explain, and make inferences about various scientific phenomena using scrapbook media so that their critical thinking skills develop. Science teachers can use scrapbook media and create it for quality science learning.Keywords: scrapbook media; critical thinking; science learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp235-247